Changing trends in epidemiology and outcome in peripartum hysterectomy over a period of ten years in a tertiary care teaching institution - Kamalakshy, Chandramathy; Chundakkadan, Mohammed Siddiq; Kalam, Suneetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Peripartum hysterectomy is a lifesaving procedure performed for severe obstetric complications such as major obstetric haemorrhage, abnormally invaded placenta, uterine rupture or sepsis. Objectives of the study was to review the epidemiology of peripartum hysterectomies performed over a period of ten years from January 2012 to December2021 and to determine the trends in peripartum hysterectomies by comparing two different time periods. Methods: In this retrospective descriptive study, the case records of peripartum hysterectomies performed at Government Medical College, Kozhikode between January 2012 and December 2021 were analysed. Results for 2012-2014 and 2019-2021 were compared to identify the changing trends. Results: Total number of deliveries for 10 years was 147272, of which 53975 (36.64%) women underwent caesarean section. Total number of peripartum hysterectomies was 312 with incidence of 2.12 per 1000 deliveries. Comparing the data of 2012-14 with 2019-21, incidence was 2.11 and 2.45 per 1000 deliveries respectively. Placenta previa accreta was the commonest indication for peripartum hysterectomies in both periods. Classical caesarean section followed by hysterectomy in 53 cases (61.62%) during 2019-21 whereas only 6 cases (6.06%) during 2012-14. Number of units of blood and blood products received was less during 2019-21 period, 56(65.11%) received only1-3 units whereas 48 (48.48%) received more than 3units during the period 2012-14. Conclusions: Placenta previa accreta was the most common indication for hysterectomy during 2019-21. Classical caesarean section followed by hysterectomy in placenta previa accreta can reduce haemorrhage and need for transfusions.